Alexithymia and Fear of Pain Independently Predict Heat Pain Intensity Ratings among Undergraduate University Students - Joel Katz; Andrea L Martin; M Gabrielle Pagé; Vincent Calleri (Pain Research and Management)
BACKGROUND: Alexithymia is a disturbance in awareness and cognitive processing of affect that is associated with over-reporting of physical symptoms, including pain. The relationship between alexithymia and other psychological constructs that are often associated with pain has yet to be evaluated.